2014
DOI: 10.1097/wno.0000000000000099
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Leak Presenting as Oculorrhea After Blunt Orbitocranial Trauma

Abstract: Cerebrospinal fluid (CSF) leak is an uncommon but well-documented occurrence after blunt head trauma, typically manifesting as otorrhea or rhinorrhea. Blunt cranio-orbital trauma also may cause CSF leak into the orbit, manifesting as orbitocele, blepharocele, chemosis, or tearing ("oculorrhea"). We report a patient who developed oculorrhea after blunt head trauma, and neuroimaging disclosed comminuted fractures of the left frontal, greater sphenoid wing, nasal, and maxillary bones. Because he also displayed ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Delaying operative intervention for other fractures is thought to minimize the risk of recurrent leaks and menegitis. [24][25][26]…”
Section: Infraorbital Nerve Entrapmentmentioning
confidence: 99%
“…Delaying operative intervention for other fractures is thought to minimize the risk of recurrent leaks and menegitis. [24][25][26]…”
Section: Infraorbital Nerve Entrapmentmentioning
confidence: 99%
“…Improved characterization of associated meningoceles is another useful feature [1,3,13,15]. Although MRC is more sensitive for active leaks, some authors have reported successful localization of intermittent or low flow leaks [9,31].…”
Section: Magnetic Resonance Imaging [Mri]mentioning
confidence: 99%
“…Approximately 80% of these patients present with rhinorrhea while the remaining 20% have otorrhea [1]. Very rarely, CSFL may present with oculorrhea [9]. Most cases [70-80%] present in the first week and almost all cases manifest clinically within the first three months [5,10,11].…”
mentioning
confidence: 99%
“…Cerebrospinal fluid (CSF) fistulas are a well-known complication of head trauma [1]. These fistulas form communications between the subarachnoid space and an internal or external cavity.…”
Section: Introductionmentioning
confidence: 99%
“…They usually are a result of fractures and dural tearing in the skull base [2], causing CSF to leak through the nasal, middle ear or orbital cavity [18]. Nasal and middle ear fistulas are a lot more common and are justified by the physical features inherent to these cavities [1,18,7]. Orbital CSF fistulas are very rare [2,16] and manifest as orbitocele, blepharocele [7], chemosis, or excessive tearing ("oculorrhea") [13,16].…”
Section: Introductionmentioning
confidence: 99%